2021
DOI: 10.2807/1560-7917.es.2021.26.11.2100256
|View full text |Cite
|
Sign up to set email alerts
|

Case fatality risk of the SARS-CoV-2 variant of concern B.1.1.7 in England, 16 November to 5 February

Abstract: The SARS-CoV-2 B.1.1.7 variant of concern (VOC) is increasing in prevalence across Europe. Accurate estimation of disease severity associated with this VOC is critical for pandemic planning. We found increased risk of death for VOC compared with non-VOC cases in England (hazard ratio: 1.67; 95% confidence interval: 1.34–2.09; p < 0.0001). Absolute risk of death by 28 days increased with age and comorbidities. This VOC has potential to spread faster with higher mortality than the pandemic to date.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(146 citation statements)
references
References 8 publications
7
131
2
1
Order By: Relevance
“… 20 Previous studies have, however, not noted any association between B.1.1.7 status and body mass index or comorbidity in patients with covid-19. 8 9 Hence, we do not expect that these potential confounders were strongly associated with SGTF status. Furthermore, they were accounted for indirectly through age, sex, ethnicity, and deprivation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 20 Previous studies have, however, not noted any association between B.1.1.7 status and body mass index or comorbidity in patients with covid-19. 8 9 Hence, we do not expect that these potential confounders were strongly associated with SGTF status. Furthermore, they were accounted for indirectly through age, sex, ethnicity, and deprivation.…”
Section: Discussionmentioning
confidence: 92%
“…2 4 5 On 18 December 2020, the variant was redesignated as a variant of concern (VOC-202012/01), and subsequent studies have found B.1.1.7 to be associated with higher mortality than other SARS-CoV-2 variants. 6 7 8 9 10…”
Section: Introductionmentioning
confidence: 99%
“…They share the N501Y mutation in RBD besides the D614G mutation around the S1/S2 cleavage site (Table 2, Figure 6). Epidemiological studies suggest that the UK variant correlates with higher viral loads in patients [306], a >40% increased epidemiological growth [307,308], a longer duration of acute infection [309], and increased severity/death rate, particularly in patients of higher age and with comorbidities [310][311][312][313]. The UK variant acquired an enhanced affinity to ACE2 [314] while maintaining sensitivity to nAb responses though with 2-9 times reduced nAb titers in vaccinees and convalescent individuals [314][315][316].…”
Section: Sars-cov-2 Mutates On a Low But Constant Level Yielding Mutant Variants Over Timementioning
confidence: 99%
“…Variant B.1.1.7 was first reported in the UK on September 2020 and by December 2020 became the dominant strain in the country (2). Its increased infectivity led to its rapid spread, with severe consequences on public health and global economy (4). Likewise, from its first detection in Israel on December 23, this variant now comprises over 90% of the positive cases (O. Erster and N. Zuckerman, Unpublished data).…”
Section: Introductionmentioning
confidence: 99%